The prevalence and correlates of syphilis and HIV among homosexual and bisexual men in Shijiazhuang, China. (February 2016) - Zhang, Shao-Hui; Liu, Shu-Jun; Hu, Ling-Ling; Li, Jie-Fang; Liu, Li-Hua; Wei, Ning
Summary: Bisexual men (men who have sex with men and women) are potential epidemiological bridges responsible for the spread of HIV and other sexually transmitted infections from men who have sex with men only to the heterosexual population. We aimed to estimate the prevalence of syphilis and HIV and the factors associated with syphilis infection among men who have sex with men and women and men who have sex with men only from Shijiazhuang, China. In 2011–2013, a cross-sectional cohort of 427 men who have sex with men was recruited by a snowball sampling method and tested for syphilis and HIV. Chi square and logistic regression were performed to identify syphilis risk factors. Among the 427 men who have sex with men, 71 (16.6%) cases were syphilis-positive and 16 cases (3.7%) were HIV-positive. The proportions of men who have sex with men and women and men who have sex with men only in the total sample were 31.4% and 68.6%, respectively. Men who have sex with men and women exhibited double the syphilis prevalence of men who have sex with men only and were more likely to practice insertive anal sex. Higher education level, being married, having more male partners, and both receptive and insertive anal sex roles were associated with syphilis among men who have sex with men and women. Residing in suburban areas, being married, being HIV positive, and an absence of desire to change sexual orientation were associated with syphilis among men who have sex with men only. Therefore, men who have sex with men and women represent an important sub-group in the syphilis epidemic and further interventions should be developed to reduce risk among different sub-sets of men who have sex with men.